Perancangan Sistem Informasi Rapor Siswa pada RA Hidayatut Tholibin Adiwerna Berbasis Website - Hidayah, Laeli; Subrata, Jaka (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
Abstract−Student Report Card Assessment Information System is a system that presents student learning outcome reports by utilizing technology. With this system, the student assessment process becomes more efficient and effective. At RA Hidayatut Tholibin, the student report card assessment system has not been computerized, it is still done manually which results in student assessments taking longer and the school does not have an archive of grades when the report cards are distributed. In this case, one of the methods used by researchers is to directly observe the ongoing assessment process at RA Hidayatut Tholibin. Researchers want to design a website-based student report card information system using the PHP programming language, codeigniter framework and MySQL as a database so that assessment information can be conveyed properly and in a structured manner. The website-based information system is expected to make it easier for teachers to manage grades and access report cards as well as the process of storing assessment information that is neater than before. The use of a website also does not require large storage on digital devices, this is one of the reasons. This design is visualized using the UML model to better understand the potential results or errors in a program. Keywords: MySQL, Design, PHP, Report Card, UML, Website